Improved Near‐Surface Continental Climate in IPSL‐CM6A‐LR by Combined Evolutions of Atmospheric and Land Surface Physics. (14th October 2020) - Cheruy, Frédérique; Ducharne, Agnès; Hourdin, Frédéric; Musat, Ionela; Vignon, Étienne; Gastineau, Guillaume; Bastrikov, Vladislav; Vuichard, Nicolas; Diallo, Binta; Dufresne, Jean‐Louis; Ghattas, Josefine; Grandpeix, Jean‐Yves; et al.
Abstract: This work is motivated by the identification of the land‐atmosphere interactions as one of the key sources of uncertainty in climate change simulations. It documents new developments in related processes, namely, boundary layer/convection/clouds parameterizations and land surface parameterization in the Earth System Model of the Institut Pierre Simon Laplace (IPSL). Simulations forced by prescribed oceanic conditions are produced with different combinations of atmospheric and land surface parameterizations. They are used to explore the sensitivity to the atmospheric physics and/or soil physics of major biases in the near surface variables over continents, the energy and moisture coupling established at the soil/atmosphere interface in not too wet (energy limited) and not too dry (moisture limited) soil moisture regions also known as transition or "hot‐spot" regions, the river runoff at the outlet of major rivers. The package implemented in the IPSL‐Climate Model for the Phase 6 of the Coupled Models Intercomparison Project (CMIP6) allows us to reduce several biases in the surface albedo, the snow cover, and the continental surface air temperature in summer as well as in the temperature profile in the surface layer of the polar regions. The interactions between soil moisture and atmosphere in hotspot regions are in better agreement with the observations. Rainfall is also significantly improved in volume and seasonality in several major river basins leading to an overall improvement in river discharge. However, the lack of consideration of floodplains and human influences in the model, for example, dams and irrigation, impacts the realism of simulated discharge. Plain Language Summary: Land surface‐atmosphere interactions play an essential role in the climate system. They strongly modulate the regional climates and have impacts on the global scale for instance through freshwater release into the oceans. Climate hazards (heat waves, droughts) and their impacts on populations also strongly depend on interactions between land and atmosphere and on their evolution with climate change. Climate models are precious tools to investigate how the Earth climate behaves. The sixth phase of the Climate Model Intercomparison Project (CMIP6) provides important tools to measure the progress and address the remaining open questions regarding the continental climate modeling. The representation of the land‐atmosphere coupled system by the IPSL‐Climate Model involved in CMIP6 is thoroughly evaluated against observations and compared with simulations using the CMIP5 version. Several biases concerning the temperature over land and over the ice sheets and with the snow cover are significantly reduced. Numerous improvements were made developping advanced parameterizations and tuning of the radiation and of the turbulent mixing in the atmospheric model. The realism of the seasonal cycle of hydrological variables such as the precipitation or the river discharge is also improved over many regions. The new treatment of hydrology paves the way for future developments on water resource aspects in the climate model. Key Points: The representation of the land‐atmosphere coupled system by the IPSL model is thoroughly evaluated Improvements with respect to previous versions are documented in the context of the Coupled Model Intercomparison Project, CMIP Advanced parameterization of land and atmospheric processes, tuning of the radiation, and the turbulent mixing yielded many improvements